Evaluasi User Experience Google Lens pada Pengguna Baru Menggunakan Metode Cognitive Walkthrough - Sari, Luky Vianika; Rosalin, Rizqi Praimadi; Mulyanto, Agus; Zamzami, Ahmad; Juliyanto, Tatang (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
New users often experience difficulties using Google Lens due to a lack of familiarity with Augmented Reality (AR) technology. This study aims to evaluate the usability of Google Lens using the Cognitive Walkthrough method, focusing on three main task scenarios: text translation, object identification, and barcode scanning. A total of 60 respondents participated in the study, with data collected through a Likert-based questionnaire (1–5) and direct observation of user interactions. The quantitative analysis results showed that Google Lens obtained an average score of 3.5 for satisfaction, 3.8 for efficiency, and 3.2 for ease of navigation. Evaluation per scenario showed the highest success rate for barcode scanning (92%), followed by text translation (85%), while object identification had the lowest success rate (78%). Qualitative findings revealed that less intuitive navigation, unclear function icons, a lack of initial guidance, and limited object identification accuracy were the main obstacles for new users. Based on these results, this study recommends several improvements, including optimizing the interface design, adding descriptive labels to icons, providing personalization features, and developing interactive tutorials for new users. With these recommendations, it is hoped that Google Lens can become an application that is easier to learn, more efficient, and provides a more satisfying experience, while also enriching the literature related to usability evaluation of Augmented Reality-based applications.